Anti-corruption Action: A Project-Based Anti-corruption Education Model During COVID-19 - Sumaryati,; Suyadi,; Nuryana, Zalik; Asmorojati, Anom Wahyu (Frontiers in Education, 2022)
Education can be used as a preventive measure to reduce the number of corruption cases during the COVID-19 pandemic. It is important to note that Anti-Corruption Education (ACE) with only cognitive knowledge is not enough and there is a need to place more emphasis on affective and psychomotor actions. Therefore, this study was used to develop a project-based learning model to package these actions based on factual learning resources in the online courses on anti-corruption during the pandemic. The focus of this participatory thematic study was on 28 students who participated in the ACE course of the Pancasila and Citizenship Education (PPKn) Study Program conducted in Ahmad Dahlan University, Indonesia, during the odd semester of 2020/2021. Data were collected using Google forms, online focus group discussions, and documentation (task reports) and analyzed through reduction, classification, and interpretation. The results showed the development of fourteen anti-corruption actions in online media with each having a different target group according to its content. This means anti-corruption learning does not stop at the realm of cognition but also extends to the affection aspect with further effects on the transformation of social media. It is important to note that the actions to prevent corruption are still needed even though the pandemic is over considering the new confirmed cases.